Quality in neonatal mortality audits: Results of pilot study from district of Dhule, Maharashtra - Bhanupriya Shivshankar Pande; Aashutosh Ramkant Patel; Amit Jagannath Patil; Shraddha Patel; Mohammed Usman Shaikh (Journal of Family Medicine and Primary Care)
Introduction: As per WHO guidelines, it is important to have quality among mortality audit documents to improve outcome in health services. Objective: To assess quality of facility-based neonatal mortality audits implementation. Methodology: Mixed-method descriptive analysis was conducted. Totally, 96 death review documents were reviewed. The 25 healthcare workers were interviewed in depth. Observation analysis done for audit meetings using WHO modified checklist for quality in audit toolkit. Results: The observation of audit meetings highlighted that almost half of the members were not communicated regarding vision of audit and framework of audit and review meetings. In quantitative analysis, it was found that secondary care hospitals were not having accuracy and consistency in audit documentation. Conclusion: The quality of neonatal death audit was poor due to challenges faced by the hospitals in creating an enabling atmosphere, which can be overcome by sharing the vision of audit with the whole staff of the hospital. A standard operating procedure for audit committee to be adopted to implement action plans. Commitment, investment, and intentional leadership from everyone, including all healthcare workers, can make these ambitious goals attainable.